Humour effects in South African advertising - Shahida Cassim; Ennis Ennis Barr Pepper iii (Communicare)
This paper develops the idea of humour as a multidimensional construct and attempts to examine its effects when used as a strategy of advertising. A conceptualisation of humour based on previous research is presented. The humour taxonomy is used to categorise a sample of advertisements appearing on South African television between 1994 and 1996. The content analysis is measured for its advertising effects by correlating the types with the noting and liking scores of South African audiences. The results confirm that different types of humour generate different advertising effects. The implications for practitioners and for researchers are explored.